Digital breast tomosynthesis-guided vacuum-assisted biopsy of suspicious calcifications at different sites within one breast: Is biopsy of more than one location needed?. Issue 154 (September 2022) - Bode, Maike; Charlotte Huck, Luisa; Raaff, Vanessa; Hitpass, Lea; Braunschweig, Till; Nebelung, Sven; Katharina Kuhl, Christiane
Highlights: Equally suspicious calcifications at distinct sites within one breast can be observed. Biopsy of more sites of calcifications can yield discordant histopathologic findings. Biopsy of more site of calcifications changes further clinical management. Abstract: Objective: To investigate how often biopsy of two sites of morphologically similar or equally suspicious calcifications within the same breast yield differing histopathologic results, and how this may affect clinical management. Materials and methods: We identified patients with two or more sites of calcifications categorized as Breast Imaging Reporting and Data System (BI-RADS) ≥ 4b within the same breast who underwent digital breast tomosynthesis-guided vacuum-assisted biopsy (DBT-guided VAB). We analyzed how often biopsy of two distinct sites yielded the same or differing histopathologic findings. The histopathologic findings were dichotomized into "actionable" and "non-actionable", depending on the respective further management. We then analyzed how often the consecutive management would have been the same or different. Results: Of 206 women undergoing DBT-guided VAB at our institution within 24 months, 21 consecutive patients (54 ± 10.2 years; range: 35–71) underwent DBT-guided VAB of two distinct sites of calcifications. Management of histologic findings was the same (both sites actionable or both sites non-actionable) in 12/21 (57 %), different in the remaining 9/21 patients (43 %). Of the nine patients whose differing histologic findings would have led to different clinical management, 4/9 had a high-risk lesion (atypical ductal hyperplasia n = 3, papilloma with epithelial atypia n = 1) vs benign changes (adenosis n = 4), 2/9 had high-grade DCIS vs benign changes (adenosis n = 1, fat necrosis n = 1), and 3/9 had invasive cancer (luminal A n = 2, luminal B n = 1) with high-grade DCIS vs pure high-grade DCIS. Conclusions: Multiple sites of calcifications within the same breast, even when morphologically similar or equally suspicious, may represent different histopathologic findings with different clinical management implications. Accordingly, in the presence of suspicious calcifications at multiple distinct sites within the same breast, biopsy of more than one site of calcification should be considered.